SEX-BASED DIFFERENCES IN THE OUTCOMES OF ACL RECONSTRUCTION WITH QUADRICEPS TENDON – PATELLAR AUTOGRAFT IN ADOLESCENT PATIENTS. Issue 3 (31st March 2019) - Gagliardi, Alexia G.; Carry, Patrick; Parikh, Harin B.; Traver, Jessica L.; Albright, Jay
Background: Female athletes suffer anterior cruciate ligament (ACL) injuries at a 2- to 10-fold greater rate than male athletes participating in the same sports. Previous research demonstrates worse patient reported outcomes and increased postoperative laxity in females with an HA autograft or BTB autograft compared to their male counterparts. Quadriceps tendon-patellar autograft has been established as a reliable graft choice for adolescent ACL reconstruction. The purpose of this study is to investigate sex-based differences in graft survival, patient reported outcomes, and joint laxity after ACL reconstruction with QPA among adolescent patients. Methods: All patients who underwent ACL reconstruction with QPA between November 2013 and November 2015 who were a minimum of 1-year post-operative were identified. Demographic data, surgical information, and graft failure was collected retrospectively. Subjects were then contacted by phone to administer International Knee Documentation Committee (IKDC) and Lysholm questionnaires. KT1000 arthrometer measurements were available for a subset of patients who attended a clinic follow-up appointment greater than 1 year postoperative. Results: The final cohort included 18 females and 20 males ages 10 to 18 years old. After adjusting for age and medial meniscus procedures, the hazard of graft failure among male athletes was 2.11 times [95% CI: 0.17 to 26.10, p = 0.5577] the hazard of failure among female athletes. No significant sex-based differences were found in time to return to sport, contralateral ACL injuries, or patient reported outcomes. KT 1000 joint laxity measurements were similar in male [median: 1 mm, IQR: 1 to 2 mm] and in female athletes [median: 1 mm, IQR: 1 to 2 mm]. After adjusting for BMI and medial meniscus procedures performed, KT1000 measurements were 8.74% higher [95% CI: 16.4% lower to 41.40% higher, p = 0.51999] in male athletes compared to female athletes. Conclusion/Significance: There were no differences between males and females in patient reported outcomes, post-operative laxity, or graft failure among subjects who underwent ACL reconstruction with QPA at a minimum of 1 year postoperative. The quadriceps tendon-patellar autograft is a reliable graft choice for both adolescent males and females. We will be completing further data collection in the next month and aim to consider subjects who are a minimum of 2 years postoperative.